Colorectal cancer incidences in Lynch syndrome: a comparison of results from the prospective lynch syndrome database and the international mismatch repair consortium - Møller, Pål; Haupt, Saskia; Knebel Doeberitz, Magnus von; Heuveline, Vincent; Ahadova, Aysel; Kloor, Matthias (Hereditary cancer in clinical practice, 2022)
To compare colorectal cancer (CRC) incidences in carriers of pathogenic variants of the MMR genes in the PLSD and IMRC cohorts, of which only the former included mandatory colonoscopy surveillance for all participants.